Viability determination data for odontoblast-like cells exposed to resin monomers (2021)
Data in this article are associated with our research article “Dental Resin Monomers Induce Early and Potent Oxidative Damage on Human Odontoblast-like Cells.” Dental adhesives are polymeric compounds consisting of several chemical substances, including resin monomers, such as 2-hydroxyethyl methacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA), together with other comonomers, making up the organic matrix of the adhesive and whose composition is based on the methyl methacrylate chemistry. The release of residual monomers, susceptible to biodegradation, acts as a source of bioactive compounds, which can interact with tissues and induce a cytotoxic cellular response. The most used techniques to evaluate cytotoxicity, proliferation, or metabolic activity of cells exposed to different substances, are MTT and resazurin. Each chemistry evaluates cell viability differently, so the data obtained could vary depending on the technique sensitivity to detect changes in cell metabolism. The objective of this article was to present viability data as a function of the metabolic activity in human odontoblast-like cells (hOLCs), exposed to 3, 6, 9, and 12 mM HEMA, or 0.75, 1.5, 3, and 6 mM TEGDMA evaluated by the MTT, and resazurin techniques in the first 24 hours of exposure, at different time points. The absorbance data for the MTT test and the fluorescence intensity for the resazurin test were obtained by spectrometry. SIMSTAT software 2.6.5 for Windows was used to confirm the normal data distribution (Levene's test). Subsequently, an analysis of variance (one-way ANOVA) was performed to compare the control with each HEMA and TEGDMA concentration. Where a p < 0.05 indicated a high F value, a Fisher's least significant differences post-hoc analysis was performed, using an alpha value < 0.05. Data from the different time points were compared with a Student's t-test for each concentration. These data may be useful to compare the cytotoxic response of hOLCs with other cell types or the cell response to other resin monomers.